2022
DOI: 10.3390/foods11142171
|View full text |Cite
|
Sign up to set email alerts
|

Effective Adsorption of Colorants from Sugarcane Juice by Bagasse-Based Biochar-Hydroxyapatite Composite

Abstract: The clarification of sugarcane juice is a crucial stage in the sugar manufacturing process, as it affects evaporator performance, sugar quality and yield. The emergence of environmentally friendly and efficient adsorption technology has resulted in widespread interest in carbon-based materials. However, their low adsorption capacity and reusability make them unsuitable for processing sugarcane juice. Here, we provide a cost-effective and sustainable method to dope hydroxyapatite (HAP) nanoparticles on porous c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…The structural integrity of E-BIDF was destroyed and its surface was uneven, forming a large number of honeycomb microstructures, which may be due to the massive degradation of wall polysaccharides caused by hemicellulase. Numerous studies have shown that the irregular surface and porous structure contribute to the adsorption capacity of the material ( 28 ), which is crucial for the subsequent adsorption of ions and molecules. Nevertheless, this special structure could increase the relative surface area, and lead to the increase of WHC, OHC, BSAC, NIAC.…”
Section: Resultsmentioning
confidence: 99%
“…The structural integrity of E-BIDF was destroyed and its surface was uneven, forming a large number of honeycomb microstructures, which may be due to the massive degradation of wall polysaccharides caused by hemicellulase. Numerous studies have shown that the irregular surface and porous structure contribute to the adsorption capacity of the material ( 28 ), which is crucial for the subsequent adsorption of ions and molecules. Nevertheless, this special structure could increase the relative surface area, and lead to the increase of WHC, OHC, BSAC, NIAC.…”
Section: Resultsmentioning
confidence: 99%
“…In recent decades, as a result of industrial increasing and technological advances, coloured effluents have caused damage to the aquatic ecosystem and posed a significant threat to human health due to their toxicity (Karaoǧlu et al, 2010;Wazir et al, 2020). To date, several techniques have been identified for the removal of dyes, including solvent extraction, photocatalytic degradation, coagulation, membrane filtration, chemical and biological oxidation and adsorption (Léonce Kouadio et al, 2022;Wang et al, 2022). Compared to other treatment systems, adsorption is an inexpensive, accessible and feasible method for the decontamination of wastewater with dyes (Al-Mahbashi et al, 2022; Blanco-Flores et al, 2016).…”
Section: Introductionmentioning
confidence: 99%